Customer oriented multi criteria decision making approach under fuzziness - Güvenç, Erdinç (My University, 2018)
Bu çalışmanın amacı, bir şirketin departmanlarının müşteri odaklı performans sıralaması için bir yapı oluşturmaktır. Bu bağlamda müşteri odaklılık, iş performansının iyileşmesine yol açtığı için, departmanların performansını değerlendirmek için müşteri odaklı çok kriterli karar verme önerilmektedir. Müşteri odaklı çok kriterli karar verme, mühendislik, otomotiv ürünleri el ve elektrikli el aletleri ve diğerlerinin tedarikçisi olan uluslararası bir şirket için gerçek bir uygulama ile yapılır. Müşteri öznel değerlendirmeleri dilsel derecelendirme olarak değerlendirilir. Kriterler, klasik 4P pazarlama karması (fiyat, ürün, yer ve tanıtım) unsurları olarak belirlenmiş ve 17 alt kriter değerlendirilmiştir. Ardından bölümlerin performansları (satış, teslimat, kalite ve bakım) sıralanır. Problemin uygulanması iki aşamaya ayrılmıştır.İlk aşamada, problem, interval type-2 AHP nin hesitant fuzzy TOPSIS ile kombine edildiği yöntem ile çözülür. Alt kriterler interval type-2 AHP ile değerlendirilir ve hesitant fuzzy TOPSIS ile performanslar sıralanır.İkinci aşamada, müşterilerin servis departmanlarının performans değerlendirmesinde tereddütlerini göz önünde bulundurmak için hesitant fuzzy kümeleri kullanılır. Müşteri yönelimi iyileştirilmiş işletme performansına yol açtığı için, müşteri yönelimini dikkate alarak şirket departmanlarının performans sıralamaları için hesitant fuzzy analitik hiyerarşi prosesi (AHP) yöntemi kullanılmaktadır.

The aim of this study is to establish a structure for customer oriented performance ranking of departments of a company. In this regard, customer oriented based multi criteria decision making (MCDM) is proposed for evaluating performance of departments since customer orientation leads to improved business performance. Customer oriented MCDM is performed with a real case application for an international company, which is the supplier of engineering, hand and power tools, automotive products, and etc. Customer subjective assessments are evaluated as linguistic ratings. The criteria are determined as elements of classical 4 Ps marketing mix (price, promotion, place, and product) and 17 sub-criteria are evaluated. Then, performances of the departments (sales, delivery, quality and maintenance) are ranked. The application of the problem is splitted into two parts.In the first part, the problem is solved by the methodology which interval type-2 fuzzy AHP is combined with hesitant fuzzy TOPSIS. The sub-criteria are evaluated by interval type-2 fuzzy AHP and the performances are ranked by hesitant fuzzy TOPSIS.In the second part, hesitant fuzzy sets are used so as to consider the customers’ hesitancy in the performances evaluation of service departments. Hesitant fuzzy analytic hierarchy process (AHP) method is utilized for performance rankings of departments of the company considering customer orientation since customer orientation leads to improved business performance.
Keywords: and etc; and product) and 17 sub-criteria are evaluated; automotive products; customer oriented based multi criteria decision making (MCDM) is proposed for evaluating performance of departments since customer orientation leads to improved business performance; Customer oriented MCDM is performed with a real case application for an international company; Customer relations; Customer services; Customer subjective assessments are evaluated as linguistic ratings; Decision making; delivery; hand and power tools; Hesitant Fuzzy AHP; Hesitant fuzzy analytic hierarchy process (AHP) method is utilized for performance rankings of departments of the company considering customer orientation since customer orientation leads to improved business performance; Hesitant Fuzzy Sets; hesitant fuzzy sets are used so as to consider the customers’ hesitancy in the performances evaluation of service departments; Hesitant Fuzzy TOPSIS; In this regard; Interval Type-2 Fuzzy AHP; Interval Type-2 Fuzzy Sets; Karar verme; Managament; Müşteri hizmetleri; Müşteri ilişkileri; Müşteri Odaklılık The aim of this study is to establish a structure for customer oriented performance ranking of departments of a company; performances of the departments (sales; Personel yönetimi; Personnel management; place; Production management; Programlı öğretim; Programmed instruction; promotion; quality and maintenance) are ranked; The application of the problem is splitted into two parts.In the first part; The criteria are determined as elements of classical 4 Ps marketing mix (price; the problem is solved by the methodology which interval type-2 fuzzy AHP is combined with hesitant fuzzy TOPSIS; The sub-criteria are evaluated by interval type-2 fuzzy AHP and the performances are ranked by hesitant fuzzy TOPSIS.In the second part; Then; Üretim yönetimi; which is the supplier of engineering; Yönetim